Treatment of textile wastewater by sulfate radical based advanced oxidation processes - Nidheesh, P.V.; Divyapriya, G.; Ezzahra Titchou, Fatima; Hamdani, Mohamed (Separation and purification technology, 2022)
[Display omitted] •Generation of SO4•- via different methods, their mechanisms and oxidative pathways.•Systematically reviewed the SR-AOPs based treatments of textile wastewater.•Comparison of the performance of SR-AOPs and other •OH radicals based AOPs.•Studies on the pilot-scale and the full-scale applications of SR-AOPs are summarized. The global textile industry is an ever-growing market, and the multi-stage operations of the textile manufacturing process produce an enormous quantity of wastewater encompassing refractory organic chemicals, necessitating the efficient, scalable, and economically viable advanced treatment methodologies. Among other advanced oxidation processes (AOPs), sulfate radicals based AOPs (SR-AOPs) gaining much attention in removing wide range of persistent organics in recent years, owing to its efficacy, adaptability, and versatility. SR-AOPs possess series of advantages over •OH radicals based AOPs such as high reactivity in wider pH range, selectivity towards contaminants, and numerous methods to activate its precursors persulfate (PS, S2O82−) and peroxymonosulfate (PMS, HSO5−) to produce sulfate radicals (SO4•-). In this review, the following aspects of the SR-AOPs are discussed for treating the textile wastewaters. (a) different methods and its mechanisms of PS and PMS activation including (i) homogenous and heterogenous metal activated processes such as metal ions, zero valent metals, metal oxides/ sulfides, and, metal organic frameworks, (ii) energy activated processes such as radiation (ultraviolet (UV), ultrasound (US) and microwave), and thermal activation, (iii) electrochemical based activation and (iv) carbocatalysis are discussed, (b) various reactive molecules and radicals species formed during the activation of PS and PMS, and its oxidative pathways and reactivities are elaborated, (c) performance of various SR-AOPs in treating textile wastewaters under different operating conditions, wastewater compositions and other influencing factors are deliberated, (d) comparison of the performances of SR-AOPs over HO• radicals based AOPs is discussed in treating the textile wastewaters and, (e) studies on the pilot-scale and the full-scale applications of SR-AOPs are summarized.